Auditor Professional Integrity Factors on Audit Quality - Julia, Julia; Darman, Darman Saputra (International Journal of Educational Research & Social Sciences, 2021)
This Study aims to determine and analyze the influence of independency, due professional care and moral reasoning on audit quality at BPK RI Representative of Bangka Belitung Province. This type of research is quantitative research with used primary research data obtained through distributing questionnaires. The population and sample of this research is all auditors at BPK RI Representative of Bangka Belitung Province. Determination of sample using saturating sampling method, which means the entire population is sample. This study uses multiple regression analysis techniques. The result of this research indicate that independency and due professional care variables have an influence on audit quality at BPK RI Representative of Bangka Belitung Province. Its shows that when the independency and due professional care getting large, the audit quality is getting high as well. Implementation with an optimal independency and due professional care will increase the realization of each part of the examination effectively and efficiently, and be able to account for the audit result properly. While, moral reasoning has not influence on audit quality at BPK RI Representative of Bangka Belitung Province.The reason is the level of moral reasoning varies depending on the understanding and perspective of each auditor so cannot be used as a determinant of the audit quality produced by an auditor